Parenting style trends before and during the COVID-19 pandemic: a bibliographic study - Nuraeni; Ayubi, Dian (Universitas Gadjah Mada, 2023)
Purpose: This bibliometric research seeks to find differences in parenting research trends before and during the COVID-19 pandemic, particularly in the distribution of publications by country, author, and publication source. In addition, we analyze the differences in collaboration networks and keywords. Methods: The data comes from the Scopus.com database with the keywords